Promotion Des Exportations Des Produits Industriels, Emploi Et Revenu Des Menages Au Maroc. Une Simulation D’impact A L’aide D’un Modele De Multiplicateurs De La Matrice De Comptabilite Sociale - Nouzha Zaoujal; Rachid El Mataoui (European Scientific Journal, ESJ, 2018)
This paper aims to analyze empirically the impact of increased exports of industrial products on employment, household income (rich, average and poor) and sectoral and global economic growth in Morocco. The methodological approach used is the multiplier techniques based on the Social Accounting Matrix (SAM). For this we use the 2015 Morocco’s SAM. The results indicate that a generally positive impact on all sectoral and macroeconomic aggregates (production, added value, employment, transactions balance and GDP). For household’s income, the results indicate also that the impact would have benefited to the average households more than rich or poor households.